2005
DOI: 10.1021/bc050237q
|View full text |Cite
|
Sign up to set email alerts
|

N-Terminally PEGylated Human Interferon-β-1a with Improved Pharmacokinetic Properties and in Vivo Efficacy in a Melanoma Angiogenesis Model

Abstract: PEGylation of IFN-alpha has been used successfully to improve the pharmacokinetic properties and efficacy of the drug. To prepare a PEGylated form of human interferon-beta-1a (IFN-beta-1a) suitable for testing in vivo, we have synthesized 20 kDa mPEG-O-2-methylpropionaldehyde and used it to modify the N-terminal alpha-amino group of the cytokine. The PEGylated protein retained approximately 50% of the activity of the unmodified protein and had significantly improved pharmacokinetic properties following intrave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
90
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(93 citation statements)
references
References 47 publications
1
90
0
2
Order By: Relevance
“…[3] Each of these methods has its own associated challenges: Selective labeling of a single cysteine residue frequently requires rounds of site-directed mutagenesis to introduce the labeling site and/or remove other cysteine residues, and selective labeling of the N-terminal amino group requires careful control of pH to ensure lysine residues are not also modified. [4] Other modern methods for chemoselective labeling often require the introduction of specific recognition sequences [5] or nonnatural amino acids into the protein to be labeled. [6] In most cases, a substantial excess of the labeling reagent is necessary to ensure complete conversion to the product.…”
mentioning
confidence: 99%
“…[3] Each of these methods has its own associated challenges: Selective labeling of a single cysteine residue frequently requires rounds of site-directed mutagenesis to introduce the labeling site and/or remove other cysteine residues, and selective labeling of the N-terminal amino group requires careful control of pH to ensure lysine residues are not also modified. [4] Other modern methods for chemoselective labeling often require the introduction of specific recognition sequences [5] or nonnatural amino acids into the protein to be labeled. [6] In most cases, a substantial excess of the labeling reagent is necessary to ensure complete conversion to the product.…”
mentioning
confidence: 99%
“…We selected the N-terminus as the site of in situ growth, because the N-terminal amine has a sufficiently different pK a (Ϸ7.8) from the amine group present on lysine side chains (pK a Ϸ 10.5-12) that are typically distributed on the protein surface. As the different pK a of the N-terminal amine allows chemical reactions to be selectively performed at the N-terminus of a protein with no cross reaction at solventaccessible lysine residues (19)(20)(21)(22)(23)(24), we hypothesized that it should be possible to selectively attach a polymerization initiator to the N-terminus and subsequently grow a polymer chain solely from the N-terminus.…”
mentioning
confidence: 99%
“…It was reported that recombinant human interferon-beta-1a with or without ribavirin has an excellent safety profile, and after 24-wk-treatment of recombinant human interferon-beta-1a with or without ribavirin, SVR was 21.6% and 27.4% in HCV genotype 1 and genotype 2 patients, respectively [57][58][59][60] . Peginterferonbeta-1a may be beneficial for patients infected with HCV [61,62] .…”
Section: Recombinant Interferon-betamentioning
confidence: 99%